Electrostatic image developing toner
Patent Information
- Application Number
- JP2022090419
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-07-12
- Filing Date
- 2022-06-02
- Publication Date
- 2025-03-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing toners for developing static loads face challenges in achieving high image quality, low-temperature fixing, and durability, particularly in terms of hot offset resistance and mechanical stability.
The development of a toner with a core-shell structure, where the shell is composed of silicone degenerative polyester resin, enhancing low-temperature fixing and durability by ensuring silicone chains are present near the toner surface and the shell uniformly covers the core, improving mechanical strength and resistance to hot offset.
The toner achieves excellent low-temperature fixing, reduces hot offset, and demonstrates improved durability by maintaining the core-shell structure even under mechanical stress, ensuring high image quality and stability.
Smart Images

Figure 2023011500000001
Abstract
Description
Technical Field
[0001] The present invention relates to a toner for developing an electrostatic charge image.
Background Art
[0002] In the field of electrophotography, with the development of electrophotographic systems, there is a demand for the development of toners for developing electrostatic charge images that can handle high image quality and high speed.
[0003] Patent Document 1 discloses an electrophotographic toner composition that aims to improve offset resistance and blocking resistance and contains a binder resin, a colorant, a silicone oil, and a silicone-modified resin.
Prior Art Documents
Patent Documents
[0004]
Patent Document 1
Summary of the Invention
Problems to be Solved by the Invention
[0005] Patent Document 1 relates to capsule toner and contains a silicone-modified resin inside the capsule, so there is room for improvement in offset resistance. The present invention relates to a toner for developing an electrostatic charge image that is excellent in low-temperature fixing property, hot offset resistance, and durability.
Means for Solving the Problems
[0006] One embodiment of the present invention relates to the following [1]. [1] A toner for developing an electrostatic charge image containing toner particles, wherein the toner particles have a core-shell structure composed of a core part and a shell part, and the shell part contains a silicone-modified polyester resin, A toner for developing an electrostatic charge image. [Effects of the Invention]
[0007] According to the present invention, it is possible to provide a toner for electrostatic image development that is excellent in low-temperature fixing properties, hot offset resistance, and durability. [Modes for carrying out the invention]
[0008] [Toner for developing electrostatic images] The electrostatic image developing toner of the present invention (hereinafter also simply referred to as "toner") is an electrostatic image developing toner containing toner particles, the toner particles having a core-shell structure consisting of a core portion and a shell portion, the shell portion containing a silicone-modified polyester resin (hereinafter also referred to as resin A). According to the present invention, it is possible to provide a toner for electrostatic image development that is excellent in low-temperature fixing properties, hot offset resistance, and durability. Furthermore, durability refers to the toner's superior mechanical strength, meaning that the core-shell structure is maintained even after prolonged agitation within the developing machine.
[0009] The detailed mechanism by which the above effects are achieved is unknown, but some of the explanations are as follows. The shell portion of the toner particles having a core-shell structure contains a silicone-modified polyester resin (resin A), which allows silicone chains to be present near the toner surface, resulting in good release properties during fixing, and consequently, excellent low-temperature fixing properties and resistance to hot offset. However, as will be described later, when manufactured by a manufacturing method that includes an aggregation step and a fusion step in an aqueous medium, silicone chains are present near the toner surface, but are considered to be almost absent on the outermost surface. Furthermore, by incorporating a silicone-modified polyester resin (silicone-modified polyester resin), which has low surface tension, into the shell portion, the shell portion becomes more easily wettable and spreads to the core portion. This allows the shell portion to uniformly cover the core portion, resulting in better formation of the core-shell structure, and consequently, improved durability.
[0010] The definitions of various terms used in this specification are shown below. Whether a resin is crystalline or amorphous is determined by its crystallinity index. The crystallinity index is defined as the ratio of the softening point of the resin to the maximum endothermic peak temperature (softening point (°C) / maximum endothermic peak temperature (°C)) in the measurement method described in the examples below. A crystalline resin is one in which the crystallinity index is 0.6 or higher and 1.4 or lower. An amorphous resin is one in which no endothermic peak is observed, or if observed, the crystallinity index is less than 0.6 or greater than 1.4. The crystallinity index can be appropriately adjusted depending on the type and ratio of raw material monomers, as well as manufacturing conditions such as reaction temperature, reaction time, and cooling rate. In this specification, the carboxylic acid component of the polyester resin includes not only the compound itself, but also anhydrides that decompose during the reaction to produce acid, and alkyl esters of each carboxylic acid (alkyl group having 1 to 3 carbon atoms). "Volume-intermediate particle size (D 50 ")" refers to the particle size at which the cumulative volume frequency calculated using volume fractions accounts for 50% of the total volume frequency, starting from the smallest particle size. The coefficient of variation of the particle size distribution (hereinafter also simply referred to as the "CV value") is a value expressed by the following formula. In the following formula, the volume-average particle size is the particle size obtained by dividing the sum of the product of the particle size and the volume of each measured particle by the total volume of the measured particles. CV value (%) = [Standard deviation of particle size distribution (μm) / Volume-average particle size (μm)] × 100 The term "carboxylic acid compound" includes not only the carboxylic acid itself, but also the anhydride that decomposes during the reaction to produce acid, and alkyl esters of each carboxylic acid (alkyl groups with 1 to 3 carbon atoms). "Bisphenol A" is 2,2-bis(4-hydroxyphenyl)propane. "Binding resin" refers to the resin components contained in the toner, including resin A, as well as resins B and C described later.
[0011] The toner of the present invention includes toner particles, and the toner has a core-shell structure. The toner may consist of, for example, only toner particles, but it is preferable that it includes toner particles and an external additive.
[0012] [Toner particles] The toner particles have a core-shell structure consisting of a core portion and a shell portion, and the shell portion contains a silicone-modified polyester resin (resin A). The binder resin of the core portion is not particularly limited, but it is preferably a polyester resin, more preferably at least an amorphous polyester resin (hereinafter also referred to as resin B), and even more preferably a crystalline polyester resin (hereinafter also referred to as resin C) and an amorphous polyester resin (hereinafter also referred to as resin B). The toner particles may also contain other additives such as release agents, colorants, charge control agents, magnetic powders, flow improvers, conductivity modifiers, reinforcing fillers such as fibrous materials, antioxidants, anti-aging agents, and cleaning properties improvers.
[0013] <Silicone-modified polyester resin (Resin A)> Resin A contains a silicone-modified polyester resin, from the viewpoint of obtaining a toner with excellent low-temperature fixability, hot-off resistance, and durability. Resin A preferably contains a reaction product of an alcohol component containing a divalent or higher alcohol, a carboxylic acid component containing a divalent or higher carboxylic acid compound, and a modified silicone having a hydroxyl group, a carboxyl group, or an epoxy group at one or both ends. Examples of polyester resins include polyester resins and composite resins containing polyester resin segments and addition polymerization resin segments. Resin A is preferably an amorphous resin.
[0014] (Alcohol content) The alcohol component includes dihydric or higher alcohols. The content of dihydric or higher alcohols is preferably 80% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and 100% by mass or less, in the alcohol component. Examples of alcohols with a valency of 2 or higher include alkylene oxide adducts of aromatic diols, linear or branched aliphatic diols, alicyclic diols, and polyhydric alcohols with a valency of 3 or higher. Among these, alkylene oxide adducts of aromatic diols or linear or branched aliphatic diols are preferred, and alkylene oxide adducts of aromatic diols are more preferred.
[0015] The alkylene oxide adduct of an aromatic diol is preferably an alkylene oxide adduct of bisphenol A, and more preferably of formula (I):
[0016] [ka] (In the formula, OR 1 and R 2 O is an oxyalkylene group, R 1 and R 2 This is an alkylene oxide adduct of bisphenol A, where each is independently an ethylene group or a propylene group, x and y represent the average number of moles of alkylene oxide added, each being a positive number, and the sum of x and y is 1 or more, preferably 1.5 or more, and 16 or less, preferably 8 or less, more preferably 4 or less. Examples of alkylene oxide adducts of bisphenol A include propylene oxide adducts of bisphenol A and ethylene oxide adducts of bisphenol A. One or more of these may be used. Among these, a combination of propylene oxide adduct and ethylene oxide adduct of bisphenol A is preferred. The molar ratio of bisphenol A propylene oxide adduct to bisphenol A ethylene oxide adduct (bisphenol A propylene oxide adduct / bisphenol A ethylene oxide adduct) is preferably 10 / 90 or more, more preferably 15 / 85 or more, even more preferably 20 / 80 or more, and preferably 90 / 10 or less, more preferably 70 / 30 or less, even more preferably 50 / 50 or less, and even more preferably 35 / 65 or less. If the alcohol component contains an alkylene oxide adduct of bisphenol A, the amount is preferably 70 mol% or more, more preferably 90 mol% or more, even more preferably 95 mol% or more, and 100 mol% or less, and even more preferably 100 mol%.
[0017] As for the linear or branched aliphatic diol, aliphatic diols having a hydroxyl group bonded to a secondary carbon atom are preferred. The aliphatic diol having a hydroxyl group bonded to a secondary carbon atom preferably has 3 to 4 carbon atoms. Examples of aliphatic diols having a hydroxyl group bonded to a secondary carbon atom include 1,2-propanediol, 1,2-butanediol, 1,3-butanediol, and 2,3-butanediol. When an aliphatic diol having a hydroxyl group bonded to a secondary carbon atom is used as the alcohol component, its amount is preferably 70 mol% or more, more preferably 90 mol% or more, even more preferably 95 mol% or more, and 100 mol% or less, and even more preferably 100 mol% of the alcohol component.
[0018] Other examples of linear or branched aliphatic diols include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, and 1,12-dodecanediol.
[0019] Examples of alicyclic diols include hydrogenated bisphenol A [2,2-bis(4-hydroxycyclohexyl)propane] and alkylene oxide adducts of hydrogenated bisphenol A with 2 to 4 carbon atoms (average number of added moles: 2 to 12). Examples of polyhydric alcohols with a valency of 3 or higher include glycerin, pentaerythritol, trimethylolpropane, and sorbitol. These alcohol components may be used individually or in combination of two or more types.
[0020] (Carboxylic acid component) The carboxylic acid component includes carboxylic acid compounds with two or more valent values. The content of divalent or greater carboxylic acid compounds is preferably 80% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and 100% by mass or less, of the carboxylic acid component. Examples of divalent or higher carboxylic acid compounds include aromatic dicarboxylic acid compounds, linear or branched aliphatic dicarboxylic acid compounds, alicyclic dicarboxylic acid compounds, and trivalent or higher polyvalent carboxylic acid compounds. Among these, aromatic dicarboxylic acid compounds are preferred.
[0021] Examples of aromatic dicarboxylic acid compounds include phthalic acid, isophthalic acid, and terephthalic acid. Among these, isophthalic acid or terephthalic acid are preferred, and terephthalic acid is more preferred. The amount of aromatic dicarboxylic acid compound is preferably 30 mol% or more, more preferably 60 mol% or more, even more preferably 80 mol% or more, even more preferably 85 mol% or more, and 100 mol% or less, in the carboxylic acid component.
[0022] The number of carbon atoms in the linear or branched aliphatic dicarboxylic acid compound is preferably 2 or more, more preferably 4 or more, even more preferably 8 or more, even more preferably 10 or more, and preferably 22 or less, more preferably 16 or less. Examples of linear or branched aliphatic dicarboxylic acid compounds include oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, adipic acid, sebacic acid, dodecanediic acid, tetradecanediic acid, succinic acid substituted with an aliphatic hydrocarbon group having 1 to 20 carbon atoms, or their anhydrides or alkyl esters having 1 to 3 carbon atoms. Examples of succinic acid substituted with aliphatic hydrocarbon groups having 1 to 20 carbon atoms include dodecyl succinic acid, dodecenyl succinic acid, and octenyl succinic acid. Among these, succinic acid substituted with aliphatic hydrocarbon groups having 1 to 20 carbon atoms, or their anhydrides, are preferred. If a linear or branched aliphatic dicarboxylic acid compound is included, its amount is preferably 2 mol% or more, more preferably 3 mol% or more, even more preferably 5 mol% or more, and preferably 30 mol% or less, more preferably 20 mol% or less, and even more preferably 10 mol% or less, of the carboxylic acid component.
[0023] The polycarboxylic acid compounds with a valency of 3 or higher are preferably trivalent carboxylic acids, such as trimellitic acid or its anhydride. Among these, trimellitic acid or its anhydride is preferred. When a polycarboxylic acid compound with a valency of 3 or higher is included, the amount of the polycarboxylic acid compound with a valency of 3 or higher is preferably 1 mol% or more, more preferably 5 mol% or more, even more preferably 8 mol% or more, even more preferably 10 mol% or more, and preferably 35 mol% or less, more preferably 30 mol% or less, in the carboxylic acid component. These carboxylic acid compounds may be used individually or in combination of two or more.
[0024] The equivalent ratio [COOH group / OH group] of the carboxyl group of the carboxylic acid component to the hydroxyl group of the alcohol component is preferably 0.7 or higher, more preferably 0.8 or higher, and preferably 1.3 or lower, more preferably 1.2 or lower.
[0025] If resin A is a composite resin having an addition polymerization resin segment, the addition polymerization resin segment is, for example, an addition polymerization product of raw material monomers containing a styrene-based compound. Examples of styrene compounds include unsubstituted or substituted styrene. Examples of substituents that can be substituted for styrene include alkyl groups having 1 to 5 carbon atoms, halogen atoms, alkoxy groups having 1 to 5 carbon atoms, sulfonic acid groups, or salts thereof. Examples of styrene-based compounds include styrene, methylstyrene, α-methylstyrene, β-methylstyrene, tert-butylstyrene, chlorostyrene, chloromethylstyrene, methoxystyrene, styrene sulfonic acid, or salts thereof. Among these, styrene is preferred. The content of styrene compounds in the raw material monomers of the addition polymerization resin segment is preferably 50% by mass or more, more preferably 65% by mass or more, even more preferably 75% by mass or more, and 100% by mass or less, preferably 95% by mass or less, more preferably 90% by mass or less, and even more preferably 85% by mass or less.
[0026] Other raw material monomers besides styrene compounds include, for example, (meth)acrylic acid esters such as alkyl (meth)acrylate, benzyl (meth)acrylate, and dimethylaminoethyl (meth)acrylate; olefins such as ethylene, propylene, and butadiene; halovinyls such as vinyl chloride; vinyl esters such as vinyl acetate and vinyl propionate; vinyl ethers such as methyl vinyl ether; vinylidene halides such as vinylidene chloride; and N-vinyl compounds such as N-vinylpyrrolidone. Among these, (meth)acrylic acid esters are preferred, and alkyl (meth)acrylate is more preferred. The number of carbon atoms in the alkyl group of (meth)acrylate is preferably 1 or more, more preferably 4 or more, even more preferably 6 or more, and preferably 24 or less, more preferably 22 or less, and even more preferably 20 or less. Examples of alkyl (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, iso(or tertiary)butyl (meth)acrylate, isoamyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, isodecyl (meth)acrylate, isododecyl (meth)acrylate, isopalmityl (meth)acrylate, isostearyl (meth)acrylate, isobehenyl (meth)acrylate, and so on. Preferably, 2-ethylhexyl (meth)acrylate or stearyl (meth)acrylate is preferred, more preferably 2-ethylhexyl acrylate, stearyl methacrylate, and even more preferably 2-ethylhexyl acrylate. Note that "(iso or tertiary)" and "(iso)" refer to both cases where these prefixes are present and where they are not, and the absence of these prefixes indicates the normal form. Also, "(meth)acrylic acid" refers to acrylic acid or methacrylic acid.
[0027] The content of (meth)acrylic acid ester in the raw material monomer of the addition polymerization resin segment is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 15% by mass or more, and preferably 50% by mass or less, more preferably 35% by mass or less, and even more preferably 25% by mass or less. The total amount of styrene compounds and (meth)acrylic acid esters in the raw material monomers of the addition polymerization resin segment is preferably 80% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and even more preferably 100% by mass.
[0028] Resin A preferably has constituent units derived from both reactive monomers that are covalently bonded to a polyester resin segment and an addition polymerization resin segment. "Constituent units derived from both reactive monomers" refers to units formed by the reaction of the functional groups and addition polymerizable groups of both reactive monomers. Examples of addition polymerizable groups include carbon-carbon unsaturated bonds (ethylenically unsaturated bonds). Examples of both reactive monomers include addition polymerizable monomers having at least one functional group selected from hydroxyl groups, carboxyl groups, epoxy groups, primary amino groups, and secondary amino groups within the molecule. Among these, addition polymerizable monomers having at least one functional group selected from hydroxyl groups and carboxyl groups are preferred from the viewpoint of reactivity, and addition polymerizable monomers having carboxyl groups are more preferred. Examples of addition polymerizable monomers having a carboxyl group include acrylic acid, methacrylic acid, fumaric acid, and maleic acid. Among these, acrylic acid and methacrylic acid are preferred from the viewpoint of reactivity in both polycondensation and addition polymerization reactions, with acrylic acid being more preferred. When both reactive monomers are addition polymerizable monomers having a carboxyl group, the amount of constituent units derived from both reactive monomers is preferably 0.1 mol or more, more preferably 0.5 mol or more, even more preferably 1 mol or more, and preferably 20 mol or less, more preferably 15 mol or less, and even more preferably 10 mol or less, per 100 mol parts of the alcohol component of the polyester resin segment of resin A.
[0029] If resin A is a composite resin, resin A may further contain, in addition to polyester resin segments and addition polymerization resin segments, constituent units derived from hydrocarbon wax having at least one of a carboxyl group and a hydroxyl group (constituent units derived from hydrocarbon wax). Examples of hydrocarbon waxes include those similar to the hydrocarbon wax in resin B described later.
[0030] (Modified silicone) The modified silicone used in resin A reacts with at least one of the alcohol component and the carboxylic acid component, and from the viewpoint of obtaining an electrophotographic toner with excellent low-temperature fixability, hot offset resistance, and durability, it is preferably a modified silicone having a hydroxyl group, a carboxyl group, or an epoxy group in the side chain, one end, or both ends, and preferably a modified silicone having one end or both ends.
[0031] More specifically, modified silicone is preferably of formula (1):
[0032] [ka] This is a modified silicone represented by the formula [wherein R is independently a hydrocarbon group having 1 to 6 carbon atoms, R' is independently an alkylene group having 1 to 10 carbon atoms, R'' is independently a hydrocarbon group having 1 to 10 carbon atoms, X is independently a hydroxyl group, a hydroxyalkyloxy group, a carboxyl group, a carboxyalkyloxy group, an epoxy group, a glycidyl group, a glycidyloxy group, or an alicyclic epoxy group, s is an integer from 1 to 3, t is an integer from 0 to 3, and n is an integer from 5 to 300.].
[0033] The number of carbon atoms in the hydrocarbon group R is 6 or less, preferably 5 or less, more preferably 4 or less, even more preferably 3 or less, even more preferably 2 or less, and even more preferably 1. Examples of hydrocarbon groups for R include methyl, ethyl, n-propyl, isopropyl, n-butyl, tert-butyl, pentyl, and phenyl groups. Among these, the methyl group is preferred. The number of carbon atoms in the alkylene group of R' is 10 or less, preferably 8 or less, more preferably 5 or less, even more preferably 4 or less, even more preferably 3 or less, and preferably 1 or more, more preferably 2 or more. Examples of the alkylene group of R' include methanediyl group, ethane-1,2-diyl group, ethane-1,1-diyl group, n-propane-1,3-diyl group, n-propane-1,2-diyl group, 2-methylethane-1,2-diyl group, 1,4-n-butyl group, 1,2-tert-butyl group, and 1,5-pentyl group. Among these, ethane-1,2-diyl group, n-propane-1,3-diyl group, and n-propane-1,2-diyl group are preferred, and n-propane-1,2-diyl group is more preferred. The number of carbon atoms in the hydrocarbon group R'' is 10 or less, preferably 8 or less, more preferably 6 or less, even more preferably 4 or less, even more preferably 3 or less, even more preferably 2 or less, and even more preferably 1. Examples of hydrocarbon groups for R'' include methyl, ethyl, n-propyl, isopropyl, n-butyl, tert-butyl, pentyl, and benzyl groups. X is a hydroxyl group, a hydroxyalkyloxy group, a carboxyl group, a carboxyalkyloxy group, an epoxy group, a glycidyl group, a glycidyloxy group, or an alicyclic epoxy group. Hydroxyalkyloxy groups and hydroxyalkyloxy groups may have multiple hydroxyl groups. A carboxyalkyloxy group may have multiple carboxyl groups. s is 3 or less, preferably 2 or less, and more preferably 1. t is 3 or less, preferably 2 or less, and more preferably 0 or 1. n is 300 or less, preferably 200 or less, more preferably 100 or less, even more preferably 50 or less, and 5 or more, preferably 8 or more, more preferably 10 or more.
[0034] The weight-average molecular weight (Mw) of the modified silicone is preferably 600 or more, more preferably 800 or more, even more preferably 1,000 or more, and preferably 20,000 or less, more preferably 10,000 or less, even more preferably 7,000 or less, even more preferably 6,000 or less, even more preferably 5,000 or less, and even more preferably 4,000 or less. The number average molecular weight (Mn) of the modified silicone is preferably 500 or more, more preferably 700 or more, still more preferably 800 or more, and preferably 10,000 or less, more preferably 5,000 or less, still more preferably 4,000 or less, and still more preferably 3,000 or less.
[0035] The kinematic viscosity of the modified silicone is preferably 10 mm 2 / s or more, more preferably 15 mm 2 / s or more, still more preferably 20 mm 2 / s or more, and preferably 500 mm 2 / s or less, more preferably 400 mm 2 / s or less, still more preferably 300 mm 2 / s or less. The kinematic viscosity of the modified silicone is measured at 25°C using a fully automatic micro kinematic viscometer (manufactured by Bisco Tech Co., Ltd.).
[0036] The functional group equivalent weight of the modified silicone is preferably 300 g / mol or more, more preferably 500 g / mol or more, still more preferably 700 g / mol or more, and preferably 5,000 g / mol or less, more preferably 4,000 g / mol or less, still more preferably 3,000 g / mol or less. Note that the functional group equivalent weight means the mass of the modified silicone per mole of the functional group.
[0037] As the modified silicone used in resin A, from the viewpoint of obtaining a toner excellent in low-temperature fixing property, hot offset resistance and durability, a modified silicone (a) having a hydroxy group at one or both ends (hereinafter also simply referred to as "modified silicone (a)") is preferable. That is, the modified silicone (a) is preferably of the formula (la):
[0038]
Chemical formula
[0039] [ka]
[0040] From the viewpoint of further improving low-temperature fixability and hot offset resistance, it is preferable that the modified silicone (a) has hydroxyl groups at both ends. In other words, from the viewpoint of further improving low-temperature fixability and hot offset resistance, it is preferable that the modified silicone (a) has R'X at both ends. 1 Each has one of the groups represented by . That is, in the above formula (1a), s and t are 1. Furthermore, from the viewpoint of further improving low-temperature fixability and durability, it is preferable that the modified silicone (a) has a hydroxyl group at one end. In other words, from the viewpoint of further improving low-temperature fixability and durability, the modified silicone (a) has one group represented by R'X1 at each end. That is, in the above formula (1a), s is 0 and t is 1. Examples of modified silicones (a) include carbinol-modified silicones with both ends (commercial products such as "X-22-160AS", "KF-6000", "KF-6001", "KF-6002", and "KF-6003" (all manufactured by Shin-Etsu Chemical Co., Ltd.)) and carbinol-modified silicones with one end (commercial products such as "X-22-170BX", "X-22-170DX", "X-22-176DX", and "X-22-176GX-A" (all manufactured by Shin-Etsu Chemical Co., Ltd.)).
[0041] As the modified silicone used in resin A, a modified silicone (b) having epoxy groups at one or both ends is also preferred from the viewpoint of obtaining a toner with excellent low-temperature fixability, hot offset resistance, and durability. In other words, modified silicone (b) is, Preferably, formula (1b):
[0042] [ka] [In the formula, R, R', R'', s, t, and n are defined the same way as in formula (1) above. X 2 Each of these is independently an epoxy group, a glycidyl group, a glycidyloxy group, or an alicyclic epoxy group. This is a modified silicone represented by [ ]. R'X 2 Examples of the group represented by include the substituents 2b-1 to 2b-3 listed below. Of these, substituent 2b-1 is preferred.
[0043] [ka]
[0044] Modified silicone (b) preferably has an epoxy group at one end, from the viewpoint of further improving low-temperature fixability, hot offset resistance, and durability. In other words, modified silicone (b) preferably has an epoxy group at one end, from the viewpoint of further improving low-temperature fixability and hot offset resistance. 2 It has one base represented by . That is, in the above equation (1b), s is 1 and t is 0. From the viewpoint of further improving low-temperature fixability, hot offset resistance, and durability, it is preferable that the modified silicone (b) has epoxy groups at both ends. In other words, from the viewpoint of further improving durability, it is preferable that the modified silicone (b) has R'X at both ends. 2 Each has one base represented by . That is, in the above formula (1b), s and t are 1. Examples of modified silicones (b) include epoxy-modified silicones with both ends (commercially available products include "KF-105", "X-22-163A", "X-22-163B", "X-22-163C", "X-22-169AS", and "X-22-169B" (all manufactured by Shin-Etsu Chemical Co., Ltd.)) and epoxy-modified silicones with one end (commercially available products include "X-22-173BX" and "X-22-173DX" (both manufactured by Shin-Etsu Chemical Co., Ltd.)).
[0045] As the modified silicone used in resin A, a modified silicone (c) having carboxyl groups at one or both ends is also preferred from the viewpoint of obtaining a toner with excellent low-temperature fixability, hot offset resistance, and durability. In other words, the modified silicone (c) is preferably of formula (1c):
[0046] [ka] [In the formula, R, R', R'', s, t, and n are defined the same way as in formula (1) above. X 3 Each of these is independently a carboxyl group or a carboxyalkyloxy group. This is a modified silicone represented by [ ]. R'X 3 Examples of the group represented by include the substituent 2c-1 shown below.
[0047] [ka]
[0048] From the viewpoint of further improving low-temperature fixability, hot offset resistance, and durability, the modified silicone (c) preferably has carboxyl groups at both ends. In other words, from the viewpoint of further improving low-temperature fixability and hot offset resistance, the modified silicone (c) preferably has R'X at both ends. 3 Each has one of the groups represented by . That is, in the above formula (1c), s and t are 1. Examples of modified silicones (c) include double-ended carboxy-modified silicones (commercial products such as "X-22-162C" and "BY16-750" (manufactured by Shin-Etsu Chemical Co., Ltd.)) and single-ended carboxy-modified silicones (commercial product such as "X-22-3710" (manufactured by Shin-Etsu Chemical Co., Ltd.)).
[0049] In the raw materials of resin A, the amount of modified silicone is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, even more preferably 1% by mass or more, even more preferably 2% by mass or more, even more preferably 2.5% by mass or more, even more preferably 4% by mass or more, and preferably 9% by mass or less, more preferably 7% by mass or less, and even more preferably 6% by mass or less, relative to the total amount of alcohol component, carboxylic acid component, and modified silicone, from the viewpoint of low-temperature fixability and hot offset resistance.
[0050] In the raw materials of resin A, the total amount of alcohol component and carboxylic acid component is preferably 91% by mass or more, more preferably 93% by mass or more, even more preferably 94% by mass or more, and preferably 99.9% by mass or less, more preferably 99% by mass or less, and even more preferably 98% by mass or less.
[0051] The above amounts are calculated based on the alcohol component, carboxylic acid component, and modified silicone, and do not take into account the amount of water removed due to condensation. Furthermore, if a modified silicone contains a hydroxyl group or a carboxyl group, it may be understood as an alcohol component or a carboxylic acid component. However, if the compound containing the hydroxyl group or carboxyl group includes a silicone skeleton, it is considered a modified silicone. For example, when calculating the total amount of alcohol and carboxylic acid components, the modified silicone containing the hydroxyl group or carboxyl group is not included in the total amount.
[0052] When resin A is a composite resin, the content of polyester resin segments in the composite resin is preferably 40% by mass or more, more preferably 60% by mass or more, even more preferably 75% by mass or more, and preferably 90% by mass or less, and more preferably 85% by mass or less, relative to the total amount of polyester resin segments and addition polymerization resin segments. Note that constituent units derived from modified silicone and constituent units derived from both reactive monomers are included in the calculation of polyester resin segments.
[0053] When resin A is a composite resin, the content of the addition polymerization resin segment in the composite resin is preferably 10% by mass or more, more preferably 15% by mass or more, and preferably 60% by mass or less, more preferably 40% by mass or less, and even more preferably 25% by mass or less, based on the total amount of the polyester resin segment and the addition polymerization resin segment.
[0054] When resin A is a composite resin, the amount of constituent units derived from both reactive monomers in the composite resin is preferably 0.1% by mass or more, more preferably 0.15% by mass or more, and preferably 5% by mass or less, more preferably 2% by mass or less, and even more preferably 1% by mass or less, relative to the total amount of the polyester resin segment and the addition polymerization resin segment.
[0055] When resin A is a composite resin, the amount of structural units derived from modified silicone in the composite resin is preferably 10 parts by mass or less, more preferably 8 parts by mass or less, and even more preferably 6 parts by mass or less, based on 100 parts by mass of the total amount of polyester resin segment and addition polymerization resin segment.
[0056] The above amounts are calculated based on the ratio of the amounts of polyester resin segment, raw material monomers for addition polymerization resin segment, both reactive monomers, modified silicone, and radical polymerization initiator, excluding the amount of dewatering due to polycondensation in the polyester resin segment, etc. When a radical polymerization initiator is used, the mass of the radical polymerization initiator is included in the calculation of the addition polymerization resin segment.
[0057] (Physical properties of resin A) The number-average molecular weight of resin A is preferably 800 or more, more preferably 1,500 or more, even more preferably 2,500 or more, and preferably 30,000 or less, more preferably 20,000 or less, even more preferably 10,000 or less, even more preferably 5,000 or less, and even more preferably 4,000 or less, from the viewpoint of obtaining excellent low-temperature fixation.
[0058] The acid value of resin A is preferably 0.1 mg KOH / g or more, more preferably 0.5 mg KOH / g or more, even more preferably 1 mg KOH / g or more, and preferably 40 mg KOH / g or less, more preferably 30 mg KOH / g or less, and even more preferably 20 mg KOH / g or less.
[0059] The softening point of resin A is preferably 70°C or higher, more preferably 90°C or higher, even more preferably 100°C or higher, and even more preferably 105°C or higher, from the viewpoint of further improving hot offset resistance and storage life, and is preferably 140°C or lower, more preferably 130°C or lower, even more preferably 120°C or lower, and even more preferably 115°C or lower, from the viewpoint of further improving low-temperature fixing performance.
[0060] The glass transition temperature of resin A is preferably 45°C or higher, more preferably 50°C or higher, and even more preferably 55°C or higher, from the viewpoint of further improving hot offset resistance and storage performance, and is preferably 80°C or lower, more preferably 70°C or lower, and even more preferably 65°C or lower, from the viewpoint of further improving low-temperature fixing performance.
[0061] The number-average molecular weight, acid value, softening point, and glass transition temperature of resin A can be appropriately adjusted depending on the type and amount of raw material monomer used, as well as manufacturing conditions such as reaction temperature, reaction time, and cooling rate. These values can be determined by the method described in the examples. Furthermore, when using two or more types of resin A in combination, it is preferable that the number average molecular weight, acid value, hydroxyl value, softening point, and glass transition temperature obtained from the mixture thereof are all within the aforementioned ranges.
[0062] (Method of manufacturing resin A) Resin A can be obtained, for example, by reacting an alcohol component, a carboxylic acid component, and a modified silicone. In this reaction, if necessary, an esterification catalyst such as di(2-ethylhexanoate)tin(II), dibutyltin oxide, or titanium diisopropylate bistriethanolamine may be used in an amount of 0.01 parts by mass to 5 parts by mass per 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component; and an esterification co-catalyst such as gallic acid (same as 3,4,5-trihydroxybenzoic acid) may be used in an amount of 0.001 parts by mass to 0.5 parts by mass per 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component. The reaction temperature is preferably 120°C or higher, more preferably 160°C or higher, even more preferably 180°C or higher, and preferably 250°C or lower, more preferably 240°C or lower. The reaction may also be carried out in an inert gas atmosphere.
[0063] If resin A is a composite resin having an addition polymerization resin segment, the composite resin can be produced by a method comprising step A, which involves polycondensation of an alcohol component and a carboxylic acid component, and step B, which is an addition polymerization step. Step A may involve a reaction similar to the reaction between the alcohol component, the carboxylic acid component, and the modified silicone described above. Process A may be performed after process B, or process B may be performed after process A, or process A and process B may be performed simultaneously. In step A, a portion of the carboxylic acid component is subjected to a polycondensation reaction, and then step B is carried out. After that, the remaining carboxylic acid component is added to the polymerization system to further advance the polycondensation reaction in step A and the polycondensation reaction with the carboxyl groups of both reactive monomers or constituent parts derived from both reactive monomers.
[0064] Examples of radical polymerization initiators for the addition polymerization in step B include peroxides such as dibutyl peroxide, persulfates such as sodium persulfate, and azo compounds such as 2,2'-azobis(2,4-dimethylvaleronitrile). The amount of radical polymerization initiator used is preferably 1 to 20 parts by mass per 100 parts by mass of raw material monomers of the addition polymerization resin segment. The addition polymerization temperature is preferably 110°C or higher, more preferably 130°C or higher, and preferably 230°C or lower, more preferably 220°C or lower, and even more preferably 210°C or lower.
[0065] The content of resin A in the shell binder resin is preferably 30% by mass or more, more preferably 50% by mass or more, even more preferably 70% by mass or more, even more preferably 90% by mass or more, and 100% by mass or less, and even more preferably 100% by mass, from the viewpoint of further improving the low-temperature fixability of the toner and resistance to hot offset.
[0066] <Amorphous polyester resin (Resin B)> The core portion of the toner particles preferably contains an amorphous polyester resin (resin B). The amorphous polyester resin (resin B) is, for example, an amorphous polyester resin containing a polycondensate of an alcohol component and a carboxylic acid component. Examples of amorphous polyester resins include polyester resins and modified polyester resins. Examples of modified polyester resins include urethane-modified polyester resins, epoxy-modified polyester resins, and composite resins containing polyester resin segments and addition polymerization resin segments. Among these, amorphous composite resins containing a polyester resin which is a polycondensate of an alcohol component and a carboxylic acid component, or a polyester resin segment which is a polycondensate of an alcohol component and a carboxylic acid component, and an addition polymerization resin segment which is an addition polymerization of a raw material monomer containing a styrene-based compound are preferred.
[0067] Examples of alcohol components include alkylene oxide adducts of aromatic diols, linear or branched aliphatic diols, alicyclic diols, and polyhydric alcohols of trivalent or higher. Among these, alkylene oxide adducts of aromatic diols are preferred from the viewpoint of obtaining a toner with excellent low-temperature fixation properties. Examples of alkylene oxide adducts of aromatic diols are the same as those exemplified in resin A.
[0068] Examples of alkylene oxide adducts of bisphenol A include propylene oxide adducts of bisphenol A [2,2-bis(4-hydroxyphenyl)propane] and ethylene oxide adducts of bisphenol A. One or more of these may be used. Among these, propylene oxide adducts of bisphenol A are preferred. The content of the bisphenol A alkylene oxide adduct is preferably 70 mol% or more, more preferably 90 mol% or more, even more preferably 95 mol% or more, and 100 mol% or less, and even more preferably 100 mol%, in the alcohol component.
[0069] Examples of linear or branched aliphatic diols, alicyclic diols, and polyhydric alcohols of trivalent or higher include those exemplified in resin A above, and the preferred ranges are also the same. These alcohol components may be used individually or in combination of two or more types.
[0070] Examples of carboxylic acid components include dicarboxylic acids and polycarboxylic acids with a valency of three or more. Examples of dicarboxylic acids include aromatic dicarboxylic acids, linear or branched aliphatic dicarboxylic acids, and alicyclic dicarboxylic acids. Among these, at least one selected from aromatic dicarboxylic acids and linear or branched aliphatic dicarboxylic acids is preferred. Examples of aromatic dicarboxylic acids include those exemplified in resin A above. Among these, isophthalic acid and terephthalic acid are preferred, with terephthalic acid being more preferred. The amount of aromatic dicarboxylic acid is preferably 20 mol% or more, more preferably 30 mol% or more, even more preferably 40 mol% or more, even more preferably 45 mol% or more, and preferably 90 mol% or less, more preferably 85 mol% or less, and even more preferably 80 mol% or less, in the carboxylic acid component.
[0071] Examples of linear or branched aliphatic dicarboxylic acids include those exemplified in resin A above. Among these, fumaric acid, sebacic acid, and succinic acid substituted with an aliphatic hydrocarbon group having 1 to 20 carbon atoms are preferred, with fumaric acid and sebacic acid being more preferred. The amount of linear or branched aliphatic dicarboxylic acid is preferably 1 mol% or more, more preferably 3 mol% or more, even more preferably 10 mol% or more, and preferably 80 mol% or less, more preferably 60 mol% or less, even more preferably 50 mol% or less, and even more preferably 45 mol% or less, in the carboxylic acid component.
[0072] Examples of polycarboxylic acids with a valency of 3 or higher include those exemplified in resin A above. Preferably, trimellitic acid or its anhydride. When a polycarboxylic acid with three or more valent properties is included, the amount of the polycarboxylic acid with three or more valent properties is preferably 3 mol% or more, more preferably 5 mol% or more, even more preferably 8 mol% or more, and preferably 30 mol% or less, more preferably 20 mol% or less, and even more preferably 15 mol% or less, in the carboxylic acid component. These carboxylic acid components may be used individually or in combination of two or more types.
[0073] The equivalent ratio [COOH group / OH group] of the carboxyl group of the carboxylic acid component to the hydroxyl group of the alcohol component is preferably 0.7 or higher, more preferably 0.8 or higher, and preferably 1.3 or lower, more preferably 1.2 or lower.
[0074] If resin B has an addition polymerization resin segment, the addition polymerization segment is, for example, an addition polymerization product of raw material monomers containing a styrene-based compound. Examples of styrene-based compounds include those exemplified in the above-mentioned resin A, and styrene is preferred. The content of styrene compounds in the raw material monomers of the addition polymerization resin segment is preferably 50% by mass or more, more preferably 65% by mass or more, even more preferably 75% by mass or more, and 100% by mass or less, preferably 95% by mass or less, more preferably 90% by mass or less, and even more preferably 85% by mass or less.
[0075] Other raw material monomers besides styrene compounds include, for example, those exemplified in resin A above, preferably 2-ethylhexyl (meth)acrylate or stearyl (meth)acrylate, more preferably 2-ethylhexyl acrylate, stearyl methacrylate, and even more preferably stearyl methacrylate.
[0076] The content of (meth)acrylic acid ester in the raw material monomer of the addition polymerization resin segment is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 15% by mass or more, and preferably 50% by mass or less, more preferably 35% by mass or less, and even more preferably 25% by mass or less. The total amount of styrene compounds and (meth)acrylic acid esters in the raw material monomers of the addition polymerization resin segment is preferably 80% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and even more preferably 100% by mass.
[0077] Resin B preferably has constituent units derived from both reactive monomers that are covalently bonded to the polyester resin segment and the addition polymerization resin segment. As for the reactive monomers, those exemplified in resin A above are similarly exemplified, and from the viewpoint of reactivity in both polycondensation and addition polymerization reactions, acrylic acid and methacrylic acid are preferred, with acrylic acid being more preferred. When both reactive monomers are addition polymerizable monomers having a carboxyl group, the amount of constituent units derived from both reactive monomers is preferably 1 mol or more, more preferably 5 mol or more, even more preferably 8 mol or more, and preferably 30 mol or less, more preferably 25 mol or less, and even more preferably 20 mol or less, per 100 mol parts of the alcohol component of the polyester resin segment of resin B.
[0078] In addition to the polyester resin segment and the addition polymerization resin segment, the resin B may further contain constituent units derived from a hydrocarbon wax having at least one of a carboxyl group and a hydroxyl group (hereinafter also referred to as hydrocarbon wax W1). The hydrocarbon wax W1 has at least one of a carboxyl group and a hydroxyl group. The hydrocarbon wax W1 may have either a hydroxyl group or a carboxyl group, or both, but from the viewpoint of improving low-temperature fixability, offset resistance, and durability, it preferably has a hydroxyl group and a carboxyl group. Hydrocarbon wax W1 can be obtained, for example, by modifying an unmodified hydrocarbon wax using a known method. Examples of raw materials for hydrocarbon wax W1 include paraffin wax, Fischer-Tropsch wax, microcrystalline wax, polyethylene wax, and polypropylene wax. Among these, paraffin wax and Fischer-Tropsch wax are preferred.
[0079] Examples of commercially available hydrocarbon waxes containing hydroxyl groups include "Unilyn 700," "Unilyn 425," and "Unilyn 550" (all manufactured by Baker Petrolite).
[0080] Examples of hydrocarbon waxes having a carboxyl group include acid-modified hydrocarbon waxes. A commercially available hydrocarbon wax containing a carboxyl group is, for example, "High Wax 1105A" (manufactured by Mitsui Chemicals, Inc.), a maleic anhydride-modified ethylene-propylene copolymer.
[0081] Examples of commercially available hydrocarbon waxes having hydroxyl and carboxyl groups include "Paracol 6420," "Paracol 6470," and "Paracol 6490" (all manufactured by Nippon Seiro Co., Ltd.).
[0082] The hydroxyl value of hydrocarbon wax W1 is preferably 35 mg KOH / g or more, more preferably 50 mg KOH / g or more, even more preferably 70 mg KOH / g or more, and preferably 180 mg KOH / g or less, more preferably 150 mg KOH / g or less, and even more preferably 120 mg KOH / g or less, from the viewpoint of improving the image density of printed materials. The acid value of the hydrocarbon wax W1 is preferably 1 mg KOH / g or more, more preferably 5 mg KOH / g or more, even more preferably 10 mg KOH / g or more, and preferably 30 mg KOH / g or less, more preferably 25 mg KOH / g or less, and even more preferably 20 mg KOH / g or less, from the viewpoint of improving the image density of the printed material.
[0083] The sum of the hydroxyl value and acid value of hydrocarbon wax W1 is preferably 35 mg KOH / g or more, more preferably 40 mg KOH / g or more, even more preferably 60 mg KOH / g or more, even more preferably 80 mg KOH / g or more, even more preferably 90 mg KOH / g or more, and preferably 210 mg KOH / g or less, more preferably 175 mg KOH / g or less, even more preferably 140 mg KOH / g or less, and even more preferably 120 mg KOH / g or less.
[0084] The number-average molecular weight of the hydrocarbon wax W1 is preferably 500 or more, more preferably 600 or more, even more preferably 700 or more, and preferably 2000 or less, more preferably 1700 or less, and even more preferably 1500 or less, from the viewpoint of improving the image density of the printed material. The hydroxyl value and acid value of hydrocarbon wax W1 are measured according to the method described in the examples. The number-average molecular weight of hydrocarbon wax W1 is measured using gel permeation chromatography with chloroform as the solvent, using polystyrene as the standard substance.
[0085] When resin B is a composite resin, the content of polyester resin segments in the composite resin is preferably 35% by mass or more, more preferably 45% by mass or more, even more preferably 50% by mass or more, and preferably 90% by mass or less, more preferably 85% by mass or less, and even more preferably 75% by mass or less, based on the total amount of polyester resin segments and addition polymerization resin segments. Note that constituent units derived from both reactive monomers are included in the calculation of polyester resin segments.
[0086] When resin B is a composite resin, the content of the addition polymerization resin segment in the composite resin is preferably 5% by mass or more, more preferably 15% by mass or more, even more preferably 25% by mass or more, and preferably 60% by mass or less, more preferably 55% by mass or less, and even more preferably 45% by mass or less, based on the total amount of the polyester resin segment and the addition polymerization resin segment. Note that the constituent units derived from both reactive monomers are included in the calculation of the polyester resin segment.
[0087] When resin B is a composite resin, the amount of constituent units derived from both reactive monomers in the composite resin is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, even more preferably 0.8% by mass or more, and preferably 10% by mass or less, more preferably 7% by mass or less, and even more preferably 4% by mass or less, relative to the total amount of the polyester resin segment and the addition polymerization resin segment.
[0088] When resin B is a composite resin, the amount of hydrocarbon wax-derived constituent units in the composite resin is preferably 10 parts by mass or less, more preferably 8 parts by mass or less, and even more preferably 6 parts by mass or less, based on 100 parts by mass of the total amount of polyester resin segment and addition polymerization resin segment.
[0089] The above amounts are calculated based on the ratio of the raw material monomers for the polyester resin segment and the addition polymerization resin segment, the two reactive monomers, and the radical polymerization initiator, excluding the amount of dehydration due to polycondensation in the polyester resin segment, etc. When a radical polymerization initiator is used, the mass of the radical polymerization initiator is included in the calculation of the addition polymerization resin segment.
[0090] Resin B may be produced, for example, by step A, in which an alcohol component and a carboxylic acid component are polycondensed. Alternatively, if resin B is a composite resin, it may be produced by a method comprising step A and step B, in which raw material monomers and both reactive monomers of an addition polymerization resin segment are addition polymerized. Steps A and B may be the same as steps A and B in the above-described method for producing resin A. If resin B is a composite resin and further contains constituent units derived from hydrocarbon wax, in step A described above, for example, a polycondensation reaction of the alcohol component and the carboxylic acid component is carried out in the presence of a hydrocarbon wax having at least one of a hydroxyl group and a carboxyl group.
[0091] In step A, if necessary, the esterification catalyst exemplified in resin A may be used in the same amount, and the esterification co-catalyst exemplified in resin A may be used in the same amount. Furthermore, when using monomers having unsaturated bonds, such as fumaric acid, in polycondensation, a radical polymerization inhibitor may be used, preferably in an amount of 0.001 parts by mass or more and 0.5 parts by mass or less, per 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component. An example of a radical polymerization inhibitor is 4-tert-butylcatechol. The temperature of the polycondensation reaction is the same as the reaction temperature in the reaction between the alcohol component, carboxylic acid component, and modified silicone shown in resin A above, and the polycondensation may be carried out in an inert gas atmosphere.
[0092] For the addition polymerization in step B, the radical polymerization initiator exemplified in resin A above may be used in the same amount. The addition polymerization temperature may be the same as the temperature mentioned in the method for producing resin A above.
[0093] (Physical properties of resin B) The softening point of resin B is preferably 70°C or higher, more preferably 90°C or higher, and even more preferably 100°C or higher. From the viewpoint of further improving low-temperature fixation, it is preferably 150°C or lower, more preferably 140°C or lower, and even more preferably 125°C or lower. The glass transition temperature of resin B is preferably 30°C or higher, more preferably 35°C or higher, and even more preferably 40°C or higher. From the viewpoint of further improving low-temperature fixation, it is preferably 80°C or lower, more preferably 70°C or lower, and even more preferably 60°C or lower.
[0094] The acid value of resin B is preferably 5 mg KOH / g or more, more preferably 10 mg KOH / g or more, even more preferably 15 mg KOH / g or more, and preferably 40 mg KOH / g or less, more preferably 35 mg KOH / g or less, and even more preferably 30 mg KOH / g or less. The softening point, glass transition temperature, and acid value of resin B can be appropriately adjusted depending on the type and amount of raw material monomer used, as well as manufacturing conditions such as reaction temperature, reaction time, and cooling rate. These values can be determined by the method described in the examples. Furthermore, when using two or more types of resin B in combination, it is preferable that the softening point, glass transition temperature, and acid value obtained from the mixture thereof are all within the aforementioned ranges.
[0095] The content of resin B relative to the total amount of binder resin in the core is preferably 40% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, even more preferably 75% by mass or more, and preferably 95% by mass or less, more preferably 90% by mass or less, and even more preferably 85% by mass or less.
[0096] <Crystalline polyester resin (Resin C)> In the toner of the present invention, it is preferable that the core portion of the toner particles contains a crystalline polyester resin (resin C), and more preferably that only the core portion contains resin C.
[0097] Resin C is, for example, a crystalline polyester resin which is a polycondensate of an alcohol component and a carboxylic acid component. Resin C is a polycondensate of an alcohol component and a carboxylic acid component. As the alcohol component, α,ω-aliphatic diols are preferred. The number of carbon atoms in the α,ω-aliphatic diol is preferably 2 or more, more preferably 4 or more, even more preferably 6 or more, and preferably 16 or less, more preferably 14 or less, and even more preferably 12 or less. Examples of α,ω-aliphatic diols include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, and 1,14-tetradecanediol. Among these, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, and 1,12-dodecanediol are preferred, with 1,10-decanediol being more preferred.
[0098] The amount of α,ω-aliphatic diol is preferably 80 mol% or more, more preferably 85 mol% or more, even more preferably 90 mol% or more, even more preferably 95 mol% or more, and 100 mol% or less, and even more preferably 100 mol%, in the alcohol component.
[0099] The alcohol component may contain other alcohol components other than α,ω-aliphatic diols. Examples of other alcohol components include aliphatic diols other than α,ω-aliphatic diols such as 1,2-propanediol and neopentyl glycol; aromatic diols such as alkylene oxide adducts of bisphenol A; and trivalent or higher alcohols such as glycerin, pentaerythritol, and trimethylolpropane. One or more of these alcohol components may be used.
[0100] As the carboxylic acid component, aliphatic dicarboxylic acids are preferred, and linear aliphatic dicarboxylic acids are more preferred. The number of carbon atoms in the aliphatic dicarboxylic acid is preferably 4 or more, more preferably 8 or more, even more preferably 10 or more, and preferably 14 or less, more preferably 12 or less. Examples of aliphatic dicarboxylic acids include fumaric acid, sebacic acid, dodecanediic acid, and tetradecanediic acid. Among these, sebacic acid and tetradecanediic acid are preferred, with sebacic acid being more preferred. One or more of these carboxylic acid components may be used.
[0101] The amount of aliphatic dicarboxylic acid is preferably 80 mol% or more, more preferably 85 mol% or more, even more preferably 90 mol% or more, even more preferably 95 mol% or more, and 100 mol% or less, and even more preferably 100 mol%, in the carboxylic acid component.
[0102] The carboxylic acid component may include other carboxylic acid components other than aliphatic dicarboxylic acids. Examples of other carboxylic acid components include aromatic dicarboxylic acids such as terephthalic acid and isophthalic acid; and polycarboxylic acids with a valency of three or more. One or more of these carboxylic acid components may be used.
[0103] The equivalent ratio [COOH group / OH group] of the carboxyl group of the carboxylic acid component to the hydroxyl group of the alcohol component is preferably 0.7 or higher, more preferably 0.8 or higher, and preferably 1.3 or lower, more preferably 1.2 or lower.
[0104] Resin C is produced, for example, by polycondensation of an alcohol component and a carboxylic acid component. During polycondensation, the esterification catalyst described above may be used in the amount described above, or the esterification co-catalyst described above may be used in the amount described above, as needed. Furthermore, when using monomers having unsaturated bonds, such as fumaric acid, in polycondensation, the radical polymerization inhibitor described above may be used in the amount described above as necessary. The temperature of the polycondensation reaction is preferably 120°C or higher, more preferably 160°C or higher, even more preferably 180°C or higher, and preferably 250°C or lower, more preferably 240°C or lower. The polycondensation may be carried out in an inert gas atmosphere.
[0105] (Physical properties of resin C) The softening point of resin C is preferably 60°C or higher, more preferably 70°C or higher, and even more preferably 80°C or higher, from the viewpoint of toner storage properties, and preferably 150°C or lower, more preferably 120°C or lower, even more preferably 100°C or lower, and even more preferably 95°C or lower, from the viewpoint of further improving low-temperature fixation properties. The melting point of resin C is preferably 50°C or higher, more preferably 60°C or higher, and even more preferably 70°C or higher, from the viewpoint of toner preservation, and preferably 100°C or lower, more preferably 90°C or lower, even more preferably 85°C or lower, and even more preferably 80°C or lower, from the viewpoint of further improving low-temperature fixation.
[0106] The acid value of resin C is preferably 5 mg KOH / g or more, more preferably 10 mg KOH / g or more, even more preferably 15 mg KOH / g or more, and preferably 35 mg KOH / g or less, more preferably 25 mg KOH / g or less, and even more preferably 20 mg KOH / g or less.
[0107] The softening point, melting point, and acid value of resin C can be appropriately adjusted depending on the type and amount of raw material monomer used, as well as manufacturing conditions such as reaction temperature, reaction time, and cooling rate, and can be determined by the method described in the examples below. When two or more types of crystalline polyester resin C are used in combination, it is preferable that the softening point, melting point, and acid value obtained as a mixture thereof are within the aforementioned ranges.
[0108] The mass ratio of resin B to resin C in the core portion [resin B / resin C] is preferably 40 / 60 or more, more preferably 60 / 40 or more, even more preferably 70 / 30 or more, even more preferably 75 / 25 or more, and preferably 95 / 5 or less, more preferably 90 / 10 or less, and even more preferably 85 / 15 or less.
[0109] <Coloring agent> In this embodiment, the toner particles preferably contain a coloring agent, and it is more preferable that the core portion contains a coloring agent. As a coloring agent, all dyes, pigments, etc. used as coloring agents for toners can be used. Examples of colorants include carbon black, phthalocyanine blue (e.g., pigment blue 15:3), permanent brown FG, brilliant first scarlet, pigment green B, rhodamine-B base, solvent red 49, solvent red 146, solvent blue 35, quinacridone, carmine 6B, and disazo yellow (e.g., pigment yellow 155). The toner may be either black toner or a color toner other than black. The colorant content is preferably 1% by mass or more, more preferably 3% by mass or more, even more preferably 4% by mass or more, and preferably 20% by mass or less, more preferably 15% by mass or less, and even more preferably 10% by mass or less, in the toner particles.
[0110] <Release agent> In this embodiment, the toner particles preferably contain a release agent, and the core portion preferably contains a release agent. Examples of release agents include polypropylene wax, polyethylene wax, polypropylene-polyethylene copolymer wax; hydrocarbon waxes such as microcrystalline wax, paraffin wax, and Fischer-Tropsch wax, or their oxides; ester waxes such as carnauba wax, montan wax, or their deoxidizing waxes, and fatty acid ester waxes; fatty acid amides, fatty acids, higher alcohols, and fatty acid metal salts. One or more of these may be used. The melting point of the release agent is preferably 60°C or higher, more preferably 65°C or higher, even more preferably 70°C or higher, and preferably 150°C or lower, more preferably 130°C or lower, and even more preferably 100°C or lower. Furthermore, when using two or more release agents in combination, it is preferable that the melting points of each wax are within the aforementioned range.
[0111] The release agent content is preferably 0.5% by mass or more, more preferably 1% by mass or more, even more preferably 2% by mass or more, and preferably 10% by mass or less, more preferably 8% by mass or less, and even more preferably 5% by mass or less, in the toner particles.
[0112] [Toner manufacturing method] Toner having toner particles having the core-shell structure described above is preferably obtained by a method comprising the following steps 1 to 3. Step 1: A step of agglomerating resin particles X containing amorphous polyester resin (resin B) and preferably crystalline polyester resin (resin C) in the same or different particles in an aqueous medium to obtain core particles (aggregated particles 1). Step 2: A step to obtain core-shell particles (aggregated particles 2) by agglomerating resin particles Y containing a silicone-modified polyester resin (resin A) with the core particles (aggregated particles 1) obtained in Step 1. Step 3: A step to obtain fused particles by heating the aggregated particles 2 obtained in Step 2 to fuse them together. In step 1, resin particles X are aggregated in an aqueous medium to obtain core particles (aggregated particles 1). Here, it is preferable that the resin particles X contain amorphous polyester resin (resin B) and crystalline polyester resin (resin C). Furthermore, it is preferable to aggregate colorant particles and release agent particles in addition to the resin particles X, and it is more preferable to mix a resin particle dispersion containing resin particles X, a colorant particle dispersion containing colorant particles, and a release agent particle dispersion containing release agent particles to aggregate these particles. The following describes each step.
[0113] Examples of methods for producing toner particles by steps 1 to 3 include steps 1, 1', and 2 described in Japanese Patent Publication No. 2021-012242, and steps 1, 1', and 2 described in Japanese Patent Publication No. 2021-026129.
[0114] In step 1 described above, it is preferable to aggregate the resin particles X with the coloring agent particles and the release agent particles containing the release agent. The dispersion of resin particles X is preferably obtained by a phase inversion emulsification method. It is preferable to incorporate the colorant particles into the core particles (aggregated particles 1) by mixing them with resin particles as a dispersion of colorant particles and agglomerating them. The colorant particle dispersion is preferably obtained by dispersing the colorant and an aqueous medium using a disperser such as a homogenizer or an ultrasonic disperser. From the viewpoint of improving the dispersion stability of the colorant, it is preferable to carry out this dispersion in the presence of a polymer dispersant or a surfactant. As a method for preparing the colorant particle dispersion, for example, the method described in Japanese Patent Application Publication No. 2021-085914 can be referred to. It is preferable to incorporate the release agent particles into the aggregated particles by mixing them with a resin particle dispersion and a coloring agent dispersion as a dispersion of release agent particles and causing aggregation. While a dispersion of release agent particles can be obtained using a surfactant, it is preferable to obtain it by mixing the release agent with resin particles Z. By preparing release agent particles using the release agent and resin particles P, the resin particles P stabilize the release agent particles, making it possible to disperse the release agent in an aqueous medium without using a surfactant. In the dispersion of release agent particles, it is thought that the release agent particles have a structure in which many resin particles P are attached to the surface. The resin constituting the resin particles P that disperse the mold release agent is preferably a polyester resin, and it is more preferable to use a composite resin D having a polyester resin segment and an addition polymerization resin segment. For details on the mold release agent particle dispersion and the composite resin D, please refer to Japanese Patent Application Publication No. 2021-026129. The dispersion of resin particles Y used in step 2 is preferably obtained by a phase inversion emulsification method. Furthermore, a post-processing step may be performed after step 3, and it is preferable to obtain toner particles by isolation. Since the particles obtained in step 3 are present in an aqueous medium, it is preferable to first perform solid-liquid separation, then wash and dry as necessary.
[0115] The mass ratio of resin particles Y to resin particles X [resin particle Y / resin particle X] is preferably 0.1 or more, more preferably 0.15 or more, even more preferably 0.2 or more, and preferably 0.45 or less, more preferably 0.4 or less, and even more preferably 0.35 or less.
[0116] [Toner particles] While toner particles obtained by drying or other processes can be used as is as toner for electrostatic image development, it is preferable to use toner particles whose surface has been treated as described later as toner for electrostatic image development. Volume-intermediate particle size of toner particles (D 50From the viewpoint of improving toner productivity and achieving both low-temperature fixability and heat-resistant storage properties of the toner, the particle size is preferably 2 μm or more, more preferably 3 μm or more, even more preferably 4 μm or more, even more preferably 5 μm or more, and preferably 10 μm or less, more preferably 8 μm or less, and even more preferably 7 μm or less. The CV value of the toner particles is preferably 12% or more, more preferably 14% or more, and even more preferably 16% or more, from the viewpoint of improving toner productivity, and preferably 32% or less, more preferably 30% or less, and even more preferably 29% or less, from the viewpoint of obtaining high-quality images. From the viewpoint of achieving both low-temperature fixability and heat-resistant storage of the toner, the circularity of the toner particles is preferably 0.955 or higher, more preferably 0.960 or higher, even more preferably 0.965 or higher, and preferably 0.990 or lower, more preferably 0.985 or lower, and even more preferably 0.980 or lower.
[0117] The mass ratio of the shell portion to the core portion in toner particles [shell portion / core portion] is preferably 0.1 or more, more preferably 0.15 or more, even more preferably 0.2 or more, and preferably 0.45 or less, more preferably 0.4 or less, and even more preferably 0.35 or less.
[0118] <External additives> While the aforementioned toner particles can be used as is as a toner for developing electrostatic images, it is preferable to use a toner that has been treated by adding a fluidizing agent or the like as an external additive to the surface of the toner particles before use as a toner for developing electrostatic images. Examples of external additives include inorganic fine particles such as hydrophobic silica, titanium dioxide fine particles, alumina fine particles, cerium oxide fine particles, and carbon black, as well as polymer fine particles such as polycarbonate, polymethyl methacrylate, and silicone resin. Among these, hydrophobic silica is preferred. External additives may be used individually or in combination of two or more. Furthermore, external additives of the same type but with different particle sizes may be used in combination. When surface treatment of toner particles is performed using an external additive, the amount of external additive added is preferably 1 part by mass or more, more preferably 2 parts by mass or more, even more preferably 3 parts by mass or more, and preferably 5 parts by mass or less, more preferably 4.5 parts by mass or less, and even more preferably 4 parts by mass or less, per 100 parts by mass of toner particles.
[0119] <Toner for developing electrostatic images> The electrostatic image developing toner obtained as described above can be used as a one-component developer, or mixed with a carrier to form a two-component developer. [Examples]
[0120] The present invention will be specifically described below with reference to examples, but the present invention is not limited in any way by these examples. The physical properties of the resin and the like were measured by the following methods. In notations such as "alkylene oxide (X)," the number X in parentheses represents the average number of moles of alkylene oxide added.
[0121] [Measurement method] [Kinematic viscosity of modified silicone] The kinematic viscosity of the modified silicones was taken from the catalog values for each product.
[0122] [Equivalent of functional groups in modified silicone] The functional group equivalents of the modified silicones were taken from the catalog values for each product.
[0123] [Acid value and hydroxyl value of resins and hydrocarbon waxes] Measurements were taken in accordance with JIS K 0070:1992, except that chloroform was used as the measurement solvent.
[0124] [Softening point, crystallinity index, melting point, and glass transition temperature of resins] (1) Softening point Using a flow tester "CFT-500D" (manufactured by Shimadzu Corporation), 1 g of sample was heated at a heating rate of 6°C / min while a load of 1.96 MPa was applied by a plunger, and the sample was extruded from a nozzle with a diameter of 1 mm and a length of 1 mm. The amount of plunger descent of the flow tester was plotted against temperature, and the temperature at which half of the sample flowed out was defined as the softening point. (2) Crystallinity index Using a differential scanning calorimeter "Q100" (manufactured by TA Instruments Japan Co., Ltd.), 0.02 g of the sample was weighed into an aluminum pan and cooled to 0°C at a cooling rate of 10°C / min. The sample was then left to stand still for 1 minute, and then heated to 180°C at a heating rate of 10°C / min, and the amount of heat was measured. Among the observed endothermic peaks, the temperature of the peak with the largest peak area was defined as the maximum endothermic peak temperature (1), and the crystallinity index was determined by (softening point (°C)) / (maximum endothermic peak temperature (1) (°C)). (3) Melting point and glass transition temperature Using a differential scanning calorimeter "Q100" (manufactured by TA Instruments Japan Co., Ltd.), 0.02 g of the sample was weighed into an aluminum pan, heated to 200°C, and then cooled to 0°C at a rate of 10°C / min. The sample was then heated again at a rate of 10°C / min, and the amount of heat was measured. Among the observed endothermic peaks, the temperature of the peak with the largest peak area was defined as the maximum endothermic peak temperature (2). In the case of crystalline resins, this peak temperature was defined as the melting point. Furthermore, in the case of amorphous resins, if a peak was observed, the temperature of that peak was defined as the glass transition temperature. If no peak was observed but a step was observed, the temperature at the intersection of the tangent line showing the maximum slope of the curve in the step portion and the extension of the baseline on the low-temperature side of the step was defined as the glass transition temperature.
[0125] [Number average molecular weight and weight average molecular weight of resins A, B, C and modified silicone] The molecular weight distribution is measured by gel permeation chromatography (GPC) using the following method, and the number-average molecular weight and weight-average molecular weight are determined. (1) Preparation of sample solution The sample is dissolved in tetrahydrofuran at 25°C to a concentration of 0.5 g / 100 mL. Then, this solution is filtered using a fluoropolymer filter "DISMIC-25JP" (manufactured by Advantec Toyo Co., Ltd.) with a pore size of 0.2 μm to remove insoluble components and obtain the sample solution. (2) Molecular weight measurement Using the measuring apparatus and analytical column described below, tetrahydrofuran is flowed as the eluent at a flow rate of 1 mL / min, and the column is stabilized in a constant temperature bath at 40°C. 100 μL of the sample solution is then injected and the measurement is performed. The molecular weight of the sample is calculated based on a calibration curve prepared in advance. The calibration curve used in this case includes several types of monodisperse polystyrene "A-500" (5.0 × 10⁻¹⁰). 2 ), "A-1000" (1.01 x 10 3 ), "A-2500" (2.63 x 10 3 ), "A-5000" (5.97 x 10 3 ), "F-1" (1.02×10 4 ), "F-2" (1.81×10 4 ), "F-4" (3.97×10 4 ), "F-10" (9.64×10 4 ), "F-20" (1.90×10 5 ), "F-40" (4.27×10 5 ), "F-80" (7.06×10 5 ), "F-128" (1.09×10 6 The above samples were prepared using Tosoh Corporation's standard samples. Measuring device: "HLC-8220GPC" (manufactured by Tosoh Corporation) Analysis columns: "GMHXL" + "G3000HXL" (both manufactured by Tosoh Corporation)
[0126] [Melting point of release agent] Using a differential scanning calorimeter "Q100" (manufactured by TA Instruments Japan Co., Ltd.), 0.02 g of the sample was weighed into an aluminum pan, heated to 200°C, and then cooled from 200°C to 0°C at a rate of 10°C / min. Next, the sample was heated again at a rate of 10°C / min, the amount of heat was measured, and the maximum peak temperature of endothermic reaction was defined as the melting point.
[0127] [Volume median particle size D of resin particles, colorant particles, and mold release agent particles] 50 [and CV value] (1) Measuring device: Laser diffraction particle size analyzer "LA-920" (manufactured by Horiba, Ltd.) (2) Measurement conditions: Take the sample dispersion into a measuring cell, add distilled water, and adjust the concentration to the appropriate range for absorbance, using a volume-average particle size D. 50 and volume-average particle size D v The following was measured. The CV value was calculated according to the following formula. CV value (%) = (Standard deviation of particle size distribution / Volume average particle size D) v ) × 100
[0128] [Solid content concentration of resin particle dispersion, colorant particle dispersion, and mold release agent particle dispersion] Using an infrared moisture meter "FD-230" (manufactured by Kett Scientific Research Institute Co., Ltd.), the moisture content (mass%) of a 5g sample was measured at a drying temperature of 150°C and measurement mode 96 (monitoring time 2.5 minutes, moisture content fluctuation range 0.05%). The solid content concentration was calculated according to the following formula. Solid content concentration (mass%) = 100-moisture (mass%)
[0129] [Volume-intermediate particle size D of aggregated particles] 50 ] Volume-intermediate particle size D of aggregated particles 50 The following measurements were taken: • Measuring instrument: "Coulter Multisizer (registered trademark) III" (manufactured by Beckman Coulter, Inc.) • Aperture diameter: 50 μm • Analysis software: "Multisizer (registered trademark) III version 3.51" (manufactured by Beckman Coulter, Inc.) • Electrolyte: "Isoton (registered trademark) II" (manufactured by Beckman Coulter, Inc.) • Measurement conditions: The sample dispersion was added to 100 mL of the electrolyte solution to adjust the concentration so that the particle size of 30,000 particles could be measured in 20 seconds. Then, 30,000 particles were measured again, and the volume median particle size D was determined from the particle size distribution. 50 They sought it.
[0130] [Circularity of fused particles] The circularity of the fused particles was measured under the following conditions. • Measurement device: Flow-type particle image analyzer "FPIA-3000" (manufactured by Sysmex Corporation) • Preparation of dispersion: The dispersion of fused particles was prepared by diluting it with deionized water to a solid content concentration of 0.001 to 0.05% by mass. • Measurement mode: HPF measurement mode
[0131] [Toner particle volume median particle size D] 50 [and CV value] Volume-intermediate particle size D of toner particles 50 The following measurements were taken: The measuring device, aperture diameter, analysis software, and electrolyte are the volume median particle size D of the aggregated particles as described above. 50 The same equipment used in the measurement was employed. • Dispersion: Polyoxyethylene lauryl ether "Emulgen® 109P" (manufactured by Kao Corporation, HLB (Hydrophile-Lipophile Balance) = 13.6) was dissolved in the electrolyte to obtain a dispersion with a concentration of 5% by mass. • Dispersion conditions: 10 mg of the measurement sample of dried toner particles was added to 5 mL of the dispersion, dispersed for 1 minute using an ultrasonic disperser, then 25 mL of the electrolyte was added, and dispersed for another minute using an ultrasonic disperser to prepare the sample dispersion. • Measurement conditions: The sample dispersion is added to 100 mL of the electrolyte to adjust the concentration to a level that allows for the measurement of 30,000 particle sizes in 20 seconds. Then, 30,000 particles are measured, and the volume median particle size D is determined from the particle size distribution. 50 and volume-average particle size D V They sought it. Furthermore, the CV value (%) was calculated according to the following formula. CV value (%) = (Standard deviation of particle size distribution / Volume average particle size D) V ) × 100
[0132] [Evaluation Method] [Toner's low-temperature fixing properties] Using high-quality paper "J Paper A4 size" (manufactured by Fuji Xerox Co., Ltd.) and a commercially available printer "Microline® 5400" (manufactured by OKI Data Corporation), the amount of toner adhering to the paper was 0.60 ± 0.01 mg / cm². 2 The resulting solid image was printed on A4 paper, leaving a 5mm margin at the top edge, and extending to a length of 50mm without being fixed. Next, a modified version of the printer with a variable-temperature fuser was prepared. The fuser temperature was set to 110°C, and toner was fixed at a rate of 1.5 seconds per sheet in the A4 portrait direction to obtain a printed document. Using a similar method, the fuser temperature was increased by 5°C increments to fix the toner and obtain printed materials. From the top margin of the printed image to the solid image, lightly attach a 50mm length of Scotch® Mending Tape 810 (manufactured by 3M Japan Ltd., 18mm wide), then place a 500g weight (contact area 1963mm²) on top. 2 A sample was placed on top and pressed back and forth once at a speed of 10 mm / s. Then, the attached tape was peeled off from the bottom end at a peeling angle of 180° and a speed of 10 mm / s to obtain the printed material after tape removal. Thirty sheets of high-quality paper "Excellent White Paper A4 size" (manufactured by OKI Data Corporation) were placed under the printed materials before and after tape application, and the reflected image density of the fixed image portion of each printed material before and after tape application was measured using a colorimeter "SpectroEye" (manufactured by Gretag Macbeth, lighting conditions: standard light source D50, observation field of view 2°, density standard DINNB, absolute white standard), and the fixing rate was calculated from each reflected image density according to the following formula. Fixation rate (%) = (Reflective image density after tape removal / Reflective image density before tape application) × 100 The lowest temperature at which the fixing rate exceeds 90% was defined as the minimum fixing temperature T1. A lower minimum fixing temperature indicates better low-temperature fixing performance.
[0133] [Toner's high-temperature fixing properties (resistance to hot offset)] Using high-quality paper "J Paper A4 size" (manufactured by Fuji Xerox Co., Ltd.) and a commercially available printer "Microline® 5400" (manufactured by OKI Data Corporation), the amount of toner adhering to the paper was 0.30 ± 0.01 mg / cm². 2 The resulting solid image was printed on A4 paper, leaving a 5mm margin at the top edge, and extending to a length of 50mm without being fixed. Next, a modified version of the printer with a variable-temperature fuser was prepared. The fuser temperature was set to 130°C, and toner was fixed at a rate of 4 seconds per sheet in A4 portrait orientation to obtain printed materials. Visual confirmation was made that no cold offset or hot offset occurred at a fuser temperature of 130°C. Using a similar method, the fuser temperature was increased by 5°C increments starting from 130°C, the toner was fixed, and printed materials were obtained. The occurrence of hot offset was visually confirmed. This test was carried out up to the temperature at which hot offset occurred. Cold offset refers to the phenomenon where toner adheres to the fuser roller when the fixing temperature is low, either because the toner on the unfixed image does not melt sufficiently or because its release properties are poor. Hot offset, on the other hand, refers to the phenomenon where toner adheres to the fuser roller when the fixing temperature is high, either because the viscoelasticity of the toner on the unfixed image decreases or because its release properties become poor at high temperatures. The occurrence of cold offset or hot offset can be determined by whether or not toner adheres to the paper again after the fuser roller has completed one rotation. In this test, it was determined by whether or not toner adhered to the area 87 mm from the top edge of the solid color image. The hot offset initiation temperature refers to the temperature at which hot offset begins to occur. Here, the highest temperature T2 at which hot offset does not occur is defined as a temperature 5°C lower than the hot offset initiation temperature. Furthermore, in the evaluation of the hot offset occurrence temperature, a difference of 5°C in the evaluation temperature clearly shows a difference in toner adhesion.
[0134] [Toner durability (time until streaks appear)] A commercially available printer, the "Microline® 5400" (manufactured by OKI Data Corporation), equipped with an ID (image drum) cartridge modified to allow visual inspection of the developing roller, was loaded with toner. Under conditions of 30°C and 80% relative humidity, the printer was run empty at 70 r / min (equivalent to 36 pages / minute). The development roller surface was visually observed every two hours for the appearance of streaks, and the time until streaks appeared was measured. The time until streaks appeared ("time when streaks appeared - 2 hours") was defined as the streak appearance time and used as an indicator of durability. A higher value indicates better durability. "Sujimura" refers to a condition where there is variation in the amount of toner adhering to the developing roller. This sujimura results in variations in image density during printing. It is believed that sujimura occurs when the toner repeatedly contacts the developing blade, causing the toner shell to detach, exposing the toner core, which then adheres to the developing blade. This adhered toner then triggers filming. Therefore, this evaluation assesses the durability against agitation within the developing machine.
[0135] [Resin manufacturing] [Manufacturing of amorphous polyester resin B1] Manufacturing example B1 (Manufacturing of resin B-1) A 10 L four-necked flask equipped with a nitrogen inlet tube, dehydration tube, stirrer, and thermocouple was purged with nitrogen. 3,253 g of bisphenol A propylene oxide (2,2) adduct, 1,003 g of terephthalic acid, 25 g of tin(II) di(2-ethylhexanoate), 2.5 g of 3,4,5-trihydroxybenzoic acid, and 394 g of hydrocarbon wax W1 "Paracol 6490" (manufactured by Nippon Seiro Co., Ltd.) were added. Under a nitrogen atmosphere, the mixture was heated to 235°C with stirring and held at 235°C for 8 hours. After that, the pressure inside the flask was reduced and held at 8 kPa for 1 hour. After returning to atmospheric pressure, the mixture was cooled to 160°C and held at 160°C. A mixture of 2,139 g of styrene, 535 g of stearyl methacrylate, 107 g of acrylic acid, and 321 g of dibutyl peroxide was added dropwise over 3 hours. The mixture was then held at 160°C for 30 minutes, then heated to 200°C, and the pressure inside the flask was reduced to 8 kPa and held for 1 hour. After returning to atmospheric pressure, it was cooled to 190°C, and 129 g of fumaric acid, 94 g of sebacic acid, 214 g of trimellitic anhydride, and 2.5 g of 4-tert-butylcatechol were added. The mixture was then heated to 210°C at a rate of 10°C / hr, and the reaction was carried out at 4 kPa until the desired softening point was reached to obtain resin B-1. The physical properties are shown in Table 1.
[0136] Manufacturing example B2 (Manufacturing of resin B-2) A four-necked flask equipped with a nitrogen inlet tube, dehydration tube, stirrer, and thermocouple was purged with nitrogen. 3558 g of propylene oxide (2.2) adduct of 2,2-bis(4-hydroxyphenyl)propane, 1,416 g of ethylene oxide (2.2) adduct of 2,2-bis(4-hydroxyphenyl)propane, 1,229 g of terephthalic acid, 1,518 g of dodecenyl succinic anhydride, and 40 g of tin(II) di(2-ethylhexanoate) were added. Under a nitrogen atmosphere, the mixture was heated to 230°C with stirring and held at 230°C for 6 hours. After that, the pressure inside the flask was further reduced and held at 8.3 kPa for 1 hour. Subsequently, the mixture was cooled to 215°C to return to atmospheric pressure. 279 g of trimellitic anhydride was added, and the mixture was held at 215°C for 1 hour. After that, the pressure inside the flask was further reduced and held at 8.3 kPa for 3 hours to obtain resin B-2. The physical properties are shown in Table 1.
[0137] Manufacturing example D1 (Manufacturing of resin D-1) A 10 L four-necked flask equipped with a nitrogen inlet tube, dehydration tube, stirrer, and thermocouple was purged with nitrogen. 4,313 g of 2,2-bis(4-hydroxyphenyl)propane propylene oxide (2,2) adduct, 818 g of terephthalic acid, 30 g of tin(II) di(2-ethylhexanoate), and 3.0 g of 3,4,5-trihydroxybenzoic acid (gallic acid) were added. Under a nitrogen atmosphere, the mixture was heated to 235°C with stirring and held at 235°C for 5 hours. After that, the pressure inside the flask was reduced and held at 8 kPa for 1 hour. After returning to atmospheric pressure, the mixture was cooled to 160°C and held at 160°C. A mixture of 2,756 g of styrene, 689 g of stearyl methacrylate, 142 g of acrylic acid, and 413 g of dibutyl peroxide was added dropwise over 3 hours. The mixture was then held at 160°C for 30 minutes, then heated to 200°C, and the pressure inside the flask was further reduced to 8 kPa and held for 1 hour. After returning to atmospheric pressure, it was cooled to 190°C, 727 g of succinic acid was added, and the temperature was raised to 210°C at a rate of 10°C / hr. The reaction was then carried out at 4 kPa until the desired softening point was reached to obtain resin D-1. The physical properties are shown in Table 1.
[0138] [Table 1]
[0139] Manufacturing example A1 (resin A-1) A 10 L four-necked flask equipped with a nitrogen inlet tube, dehydration tube, stirrer, and thermocouple was purged with nitrogen. 1,380 g of bisphenol A propylene oxide (2.2) adduct, 4,059 g of bisphenol A ethylene oxide (2.2) adduct, 2,182 g of terephthalic acid, 374 g of silicone "X-22-170BX" (manufactured by Shin-Etsu Chemical Co., Ltd.), and 40 g of tin(II) di(2-ethylhexanoate) were added. Under a nitrogen atmosphere, the mixture was heated to 235°C with stirring and held at 235°C for 6 hours. After that, the pressure inside the flask was reduced and held at 8 kPa for 1 hour. Then, after returning to atmospheric pressure, the mixture was cooled to 210°C, 379 g of trimellitic anhydride was added and reacted for 1 hour. After that, the pressure inside the flask was reduced and the reaction was carried out at 8 kPa until the desired softening point was reached to obtain resin A-1. The physical properties are shown in Table 2.
[0140] Manufacturing examples A2~A4, A81, A82 (resin A-2~A-4, resin A-81, A-82) Resins A-2 to A-4, A-81, and A-82 were obtained in the same manner as in manufacturing example B1, except that the raw material composition was changed as shown in Table 2. The physical properties are shown in Table 2.
[0141] Manufacturing example A5 (resin A-5) A 10 L four-necked flask equipped with a nitrogen inlet tube, dehydration tube, stirrer, and thermocouple was purged with nitrogen. 1,046 g of bisphenol A propylene oxide (2.2) adduct, 3,076 g of bisphenol A ethylene oxide (2.2) adduct, 1,716 g of terephthalic acid, and 371 g of silicone "X-22-170BX" (manufactured by Shin-Etsu Chemical Co., Ltd.) were added. Under a nitrogen atmosphere, the mixture was heated to 160°C while stirring, and while maintaining the temperature at 160°C, a mixture of 1,116 g of styrene, 245 g of 2-ethylhexyl acrylate, 27 g of acrylic acid, and 54 g of dibutyl peroxide was added dropwise over 1 hour. After maintaining the temperature at 160°C for 30 minutes, the temperature was raised to 200°C, and the pressure inside the flask was further reduced to 8 kPa and maintained for 1 hour. After returning to atmospheric pressure, 30 g of tin(II) di(2-ethylhexanoate) and 3.0 g of 3,4,5-trihydroxybenzoic acid were added, the temperature was raised to 235°C, and the mixture was held at 235°C for 8 hours. Then, the pressure in the flask was reduced and held at 8 kPa for 1 hour. After returning to atmospheric pressure, the mixture was cooled to 190°C, 215 g of trimellitic anhydride was added, the temperature was raised to 210°C at 10°C / hr, and the reaction was carried out at 4 kPa until the desired softening point was reached to obtain resin A-5. The physical properties are shown in Table 2.
[0142] The various silicones used in Table 2 have the following composition. X-22-170BX: Modified silicone oil "X-22-170BX" (silicone having a carbinol group at one end [as described above, silicone (a) (in formula (1a), R=CH3, and only one end is the group represented by formula (2a-1), s=1, t=0)], kinematic viscosity (25℃) 40 mm 2 ( / s, number-average molecular weight Mn 1,900, weight-average molecular weight Mw 3,500, functional group equivalent 2,800 g / mol, manufactured by Shin-Etsu Chemical Co., Ltd.) KF-6001: Modified silicone oil "KF-6001" (silicone having carbinol groups at both ends [as described above, silicone (a) (in formula (1a), R=CH3, both ends are groups represented by formula (2a-1), s=1, t=1)], kinematic viscosity (25℃) 45 mm 2( / s, number-average molecular weight Mn 1,800, weight-average molecular weight Mw 2,700, functional group equivalent 900 g / mol, manufactured by Shin-Etsu Chemical Co., Ltd.) KF96-100cs: Silicone oil "KF96-100cs" (Silicone oil, kinematic viscosity (25℃) 100mm) 2 (Manufactured by Shin-Etsu Chemical Co., Ltd.)
[0143] [Table 2]
[0144] [Manufacturing of crystalline polyester resin C-1] Manufacturing example C1 (Manufacturing of resin C-1) A 10 L four-necked flask equipped with a nitrogen inlet tube, dehydration tube, stirrer, and thermocouple was purged with nitrogen. 3,416 g of 1,10-decanediol and 4,084 g of sebacic acid were added, and the mixture was heated to 135°C while stirring. After holding at 135°C for 3 hours, the temperature was raised from 135°C to 200°C over 10 hours. Subsequently, 23 g of tin(II) di(2-ethylhexanoate) was added, and the mixture was held at 200°C for another hour. The pressure inside the flask was then reduced to 8 kPa and held under reduced pressure for 1 hour to obtain resin C-1. The physical properties are shown in Table 3.
[0145] [Table 3]
[0146] [Manufacturing of resin particle dispersions] Manufacturing Example X1 (Manufacturing of Resin Particle Dispersion X-1) In a 3L container equipped with a stirrer, reflux condenser, dropping funnel, thermometer, and nitrogen inlet tube, 240g of resin B-1, 60g of resin C-1, 300g of methyl ethyl ketone, and 59g of deionized water were placed, and the resins were dissolved at 73°C for 2 hours. To the resulting solution, a 5% by mass aqueous sodium hydroxide solution was added to achieve a degree of neutralization of 60 mol% relative to the acid value of the resin, and the mixture was stirred for 30 minutes. Next, while maintaining the temperature at 73°C, 600 g of deionized water was added over 60 minutes while stirring at 280 r / min (circumferential speed 88 m / min) to induce phase inversion emulsification. While continuing to maintain the temperature at 73°C, methyl ethyl ketone was removed under reduced pressure to obtain an aqueous dispersion. Then, while stirring at 280 r / min (circumferential speed 63 m / min), the aqueous dispersion was cooled to 30°C, and deionized water was added to achieve a solid content concentration of 20% by mass to obtain resin particle dispersion X-1. The obtained resin particle medium particle size D 50 The corresponding CV values are shown in Table 4-1.
[0147] Manufacturing Example X2 (Manufacturing of Resin Particle Dispersion X-2) Resin particle dispersion X-2 was obtained in the same manner as in production example X1, except that the type of resin used was changed as shown in Table 4-1. The median volume particle size D of the obtained resin particles 50 The corresponding CV values are shown in Table 4-1.
[0148] [Table 4-1]
[0149] Manufacturing Example Y1 (Manufacturing of resin particle dispersion Y-1) A 3L container equipped with a stirrer, reflux condenser, dropping funnel, thermometer, and nitrogen inlet tube contained a mixed solvent of 300g of resin A-1, 300g of methyl ethyl ketone, and 41g of deionized water, and the resin was dissolved at 73°C for 2 hours. To the resulting solution, a 5% by mass aqueous sodium hydroxide solution was added to achieve a degree of neutralization of 55 mol% relative to the acid value of the resin, and the mixture was stirred for 30 minutes. Next, while maintaining the temperature at 73°C, 600 g of deionized water was added over 60 minutes while stirring at 280 r / min (circumferential speed 88 m / min) to induce phase inversion emulsification. While continuing to maintain the temperature at 73°C, methyl ethyl ketone was removed under reduced pressure to obtain an aqueous dispersion. Subsequently, the aqueous dispersion was cooled to 30°C while stirring at 280 r / min (circumferential speed 88 m / min), and then deionized water was added to achieve a solid content concentration of 20% by mass to obtain resin particle dispersion Y-1. The median particle size D of the obtained resin particles... 50The corresponding CV values are shown in Table 4-2.
[0150] Manufacturing Examples: Y2~Y5, Y81, Y82 (Manufacturing of resin particle dispersions Y-2~Y-5, Y-81, Y-82) Except for changing the type of resin used as shown in Table 4-2, resin particle dispersions Y-2 to Y-5, Y-81, and Y-82 were obtained in the same manner as in production example Y1. The median volume particle size D of the obtained resin particles 50 The corresponding CV values are shown in Table 4-2.
[0151] [Table 4-2]
[0152] Manufacturing Example P1 (Manufacturing of Resin Particle Dispersion P-1) In a 3L container equipped with a stirrer, reflux condenser, dropping funnel, thermometer, and nitrogen inlet tube, 200g of resin D-1 and 200g of methyl ethyl ketone were placed, and the resin was dissolved at 73°C for 2 hours. To the resulting solution, a 5% by mass aqueous sodium hydroxide solution was added to achieve a degree of neutralization of 60 mol% relative to the acid value of the resin, and the mixture was stirred for 30 minutes. Next, while maintaining the temperature at 73°C, 700 g of deionized water was added over 50 minutes while stirring at 280 r / min (peripheral speed 88 m / min) to induce phase inversion emulsification. While continuing to maintain the temperature at 73°C, methyl ethyl ketone was removed under reduced pressure to obtain an aqueous dispersion. Subsequently, the aqueous dispersion was cooled to 30°C while stirring at 280 r / min (peripheral speed 88 m / min), and then deionized water was added to achieve a solid content concentration of 20% by mass to obtain resin particle dispersion P-1. The obtained resin particle medium particle size D 50 The particle size was 0.09 μm, and the CV value was 23%.
[0153] [Manufacturing of mold release agent particle dispersion] Manufacturing Example W1 (Manufacturing of Release Agent Particle Dispersion W-1) In a 1L beaker, 120g of deionized water, 86g of resin particle dispersion P-1, and 40g of paraffin wax "HNP-9" (manufactured by Nippon Seiro Co., Ltd., melting point 75°C) were added. The mixture was melted while maintaining a temperature of 90-95°C and stirred to obtain a molten mixture. The obtained molten mixture was further dispersed for 20 minutes using an ultrasonic homogenizer "US-600T" (manufactured by Nippon Seiki Seisakusho Co., Ltd.) while maintaining the temperature at 90-95°C, and then cooled to room temperature (20°C). Deionized water was added to adjust the solid content concentration to 20% by mass to obtain release agent particle dispersion W-1. The median particle size D of the release agent particles in the dispersion was... 50 The particle size was 0.47 μm, and the CV value was 27%.
[0154] [Production of addition polymer E] Manufacturing Example E1 (Synthesis of Addition Polymer E-1) The types and quantities of raw material monomers shown in Table 5 were mixed to prepare a monomer mixture with a total monomer content of 100 g. A four-necked flask equipped with a nitrogen inlet tube, dropping funnel, stirrer, and thermocouple was purged with nitrogen, and 18 g of methyl ethyl ketone, 0.03 g of 2-mercaptoethanol, and 10% by mass of the monomer mixture were added. The mixture was heated to 75°C while stirring. While maintaining the temperature at 75°C, the remaining 90% by mass of the monomer mixture, along with 0.27 g of 2-mercaptoethanol, 42 g of methyl ethyl ketone, and 3 g of 2,2'-azobis(2,4-dimethylvaleronitrile) "V-65" (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added dropwise from the dropping funnel over 3 hours. After the addition was complete, the mixture was maintained at 75°C for 2 hours. Then, a solution of 3 g of V-65 dissolved in 5 g of methyl ethyl ketone was added, and the mixture was maintained at 75°C for 2 hours and then at 80°C for 2 hours. Subsequently, the methyl ethyl ketone was removed by distillation under reduced pressure to obtain addition polymer E-1. Table 5 shows the weight-average molecular weight of the obtained addition polymers.
[0155] [Table 5]
[0156] [Manufacturing of colorant particle dispersion] Manufacturing Example Z1 (Manufacturing of Colorant Particle Dispersion Z-1) In a 5L container equipped with a stirrer with a disperser blade, reflux condenser, dropping funnel, thermometer, and nitrogen inlet tube, 75g of addition polymer E-1 and 630g of methyl ethyl ketone were placed and the resin was dissolved at 20°C. To the resulting solution, 101g of 5% by mass sodium hydroxide aqueous solution (to neutralize addition polymer E-1 to 91 mol%) was added, followed by 955g of deionized water, and the mixture was stirred with a disperser blade at 20°C for 10 minutes. Next, 300g of pigment yellow 155 (Toner Yellow 3GP-CT, molecular weight 717, manufactured by Clariant Chemicals Co., Ltd.) was added, and the mixture was stirred with a disperser blade at 6400 r / min at 20°C for 2 hours. After that, the mixture was passed through a 200-mesh filter and subjected to 15 passes at a pressure of 150 MPa using a homogenizer "Microfluidizer M-110EH" (manufactured by Microfluidics). The obtained dispersion was stirred and the methyl ethyl ketone and some water were removed under reduced pressure at 70°C. After cooling, it was passed through a 200-mesh filter, and deionized water was added to obtain a colorant particle dispersion Z-1 by reducing the solid content to 20% by mass. The median volume particle size D of the obtained colorant particles 50 The particle size was 0.10 μm, and the CV value was 28%.
[0157] [Toner manufacturing] Example 1 (Manufacturing of Toner 1) Toner 1 creation In a 3L four-necked flask equipped with a dewatering tube, a stirrer, and a thermocouple, 500g of resin particle dispersion X-1, 21g of mold release agent particle dispersion W-1, 63g of coloring agent particle dispersion Z-1, and 3.3g of 15% by mass sodium dodecylbenzenesulfonate aqueous solution "Neoperex G-15" (manufactured by Kao Corporation, anionic surfactant) were mixed at 25°C. Next, while stirring the mixture, a solution prepared by dissolving 40g of ammonium sulfate in 570g of deionized water and adding a 4.8% by mass potassium hydroxide aqueous solution to adjust the pH to 8.4 was added dropwise over 10 minutes at 25°C, and the temperature was raised to 61°C over 2 hours to determine the volume-median particle size D of the aggregated particles. 50The mixture was maintained at 61°C until it reached a size of 5.8 μm, and a dispersion of core particles (1) was obtained. While maintaining the temperature of the dispersion of the core particles (1) at 61°C, 60 g of resin particle dispersion Y-1 was added dropwise at a rate of 0.6 mL / min to obtain a dispersion of core-shell particles (1). To the dispersion of the obtained core-shell particles (1), an aqueous solution was added, which consisted of 20 g of polyoxyethylene lauryl ether sodium sulfate "Emal E-27C" (manufactured by Kao Corporation, anionic surfactant, effective concentration 27% by mass), 280 g of deionized water, and 40 g of 0.1 mol / L sulfuric acid aqueous solution. The mixture was then heated to 75°C over 1 hour, held at 80°C for 30 minutes, and then 15 g of 0.1 mol / L sulfuric acid aqueous solution was added, followed by another 15 g of 0.1 mol / L sulfuric acid aqueous solution. The mixture was then held at 80°C until the circularity reached 0.970, thereby obtaining a dispersion of fused particles in which the core-shell particles had fused together. The obtained fused particle dispersion was cooled to 30°C, and the dispersion was filtered by suction to separate the solid components. The dispersion was then washed with deionized water at 25°C and filtered by suction at 25°C for 2 hours. Subsequently, toner particles were obtained by vacuum drying at 33°C for 24 hours using a vacuum constant-temperature dryer "DRV622DA" (manufactured by ADVANTEC). 100 parts by mass of toner particles, 2.5 parts by mass of hydrophobic silica "RY50" (manufactured by Nippon Aerosil Co., Ltd., number average particle size: 0.04 μm), and 1.0 part by mass of hydrophobic silica "Cabosil® TS720" (manufactured by Cabot Japan Co., Ltd., number average particle size: 0.012 μm) were placed in a Henschel mixer and stirred, and passed through a 150-mesh sieve to obtain toner 1. The obtained toner had a particle size of 5.9 μm and a circularity of 0.970.
[0158] Examples 2-6 and Comparative Examples 1 and 2 (Manufacturing of Toners 2-6, 81, and 82) Toners 2-6, 81, and 82 were prepared in the same manner as in Example 1, except that the type of resin particle dispersion used was changed as shown in Table 6. The physical properties of the obtained toner particles and the evaluation results of the toners are shown in Table 6.
[0159] [Table 6]
[0160] From the results of Examples 1-6 and Comparative Examples 1-2, it can be seen that the present invention provides a toner with excellent low-temperature fixability, hot offset resistance, and durability.
Claims
1. A toner for developing an electrostatic image, comprising toner particles, The toner particles have a core-shell structure consisting of a core portion and a shell portion, The shell portion contains a silicone-modified polyester resin. Toner for developing electrostatic images.
2. 2. The toner for developing electrostatic images according to claim 1, wherein the silicone-modified polyester resin contains a reaction product of an alcohol component containing a divalent or higher alcohol, a carboxylic acid component containing a divalent or higher carboxylic acid compound, and a modified silicone having a hydroxy group, a carboxy group, or an epoxy group at one end or both ends.
3. The modified silicone has the formula (1): 【Chemistry 1】 3. The toner for developing electrostatic images according to claim 2, comprising a modified silicone represented by the following formula: (wherein R is independently a hydrocarbon group having from 1 to 6 carbon atoms, R' is independently an alkylene group having from 1 to 10 carbon atoms, R'' is independently a hydrocarbon group having from 1 to 10 carbon atoms, X is independently a hydroxy group, a hydroxyalkyloxy group, a carboxy group, a carboxyalkyloxy group, an epoxy group, a glycidyl group, a glycidyloxy group, or an alicyclic epoxy group, s is an integer of from 1 to 3, t is an integer of from 0 to 3, and n is an integer of from 5 to 300).
4. 3. The toner for developing electrostatic images according to claim 2, wherein the modified silicone has a hydroxyl group at one or both ends.
5. 3. The toner for developing electrostatic images according to claim 2, wherein a content of the modified silicone is 0.1% by mass or more and 9% by mass or less with respect to a total amount of the alcohol component, the carboxylic acid component, and the modified silicone.
6. 6. The toner for developing electrostatic images according to claim 1, wherein the core portion contains a polyester resin.